Closed system processing variables affect post‐thaw quality characteristics of cryopreserved red cell concentrates. Issue 12 (5th October 2022) - Howell, Anita; Turner, Tracey R.; Hansen, Adele; Lautner, Larissa J.; Yi, Qilong; Acker, Jason P.
Abstract: Background: Differences in manufacturing conditions using the Haemonetics ACP 215 cell processor result in cryopreserved red cell concentrates (RCCs) of varying quality. This work studied the effect of processing method, additive solution, and storage duration on RCC quality to identify an optimal protocol for the manufacture of cryopreserved RCCs. Materials and methods: RCCs were pooled‐and‐split and stored for 7, 14, or 21 days before cryopreservation. Units were glycerolized with the ACP 215 using a single or double centrifugation method. After thawing, the RCCs were deglycerolized, suspended in AS‐3, SAGM, ESOL, or SOLX/AS‐7, and stored for 0, 3, 7, 14, or 21 days before quality testing. Quality assessments included hemoglobin content, hematocrit, hemolysis, adenosine triphosphate (ATP), supernatant potassium, and mean cell volume. Results: Both glycerolization methods produced RCCs that met regulatory standards for blood quality. Dual centrifugation resulted in higher hemoglobin content, fewer processing alerts, and a shorter deglycerolization time than single centrifugation processing. Units processed with AS‐3 and ESOL met regulatory standards when stored for up to 21 days pre‐cryopreservation and 21 days post‐deglycerolization. However, ESOL demonstrated superior maintenance of ATP over RBCs in AS‐3. Some RCCs suspended in SAGM and SOLX exceeded acceptable hemolysis values after 7 days of post‐deglycerolization storage regardless of pre‐processing storage length. Conclusions: When manufacturing cryopreserved RCCs using the ACP 215, dual centrifugation processing with AS‐3 or ESOL additive solutions is preferred, with storage periods of up to 21 days both pre‐processing and post‐deglycerolization.